Activity based learning during Mathematics Classes - Aliyeva, Mujgan; Aghayeva, Nigar (ADA University, 2021)
The purpose of the study was to explore students’ and instructors’ perceptions about teaching and learning Math and pilot the Capstone Project’s end product Activity Toolbox designed to teach Trigonometric functions unit via activity-based learning approach. Qualitative research design was applied in this study. The research sought to receive an answer to the research question, “Does using of activity-based learning engage students in learning Mathematics and assist teachers in instructing them?” The first stage consisted of semi structured individual interviews conducted with four Math teachers to generate information about teaching and learning Mathematics and activity-based learning. Two focus group interviews administered with the 10th graders aimed at collecting high-quality data in a social context and understanding the specific problem, teaching Trigonometric functions unit. Second stage of the study was piloting activities from the Activity Toolbox. Types of activities were chosen considering Math teachers’ and 10th graders’ answers obtained during the interview process and then, designed. ADA School Math instructors piloted random activities from the Toolbox while teaching the tenth graders in the on-line classes, and we observed them. After the observations, interviews with the same instructors after the piloting assisted to gather their reflections about activity-based learning and piloted activities. To validate the data obtained from the observations and post -piloting interviews with the Math teachers, data triangulation was applied. The major finding of the Capstone Project was that ABL may have positively affected the tenth graders’ Math learning at ADA School based on the results of observations and Math teachers’ post- piloting interviews. The study allowed to conclude that Instructions Checking Questions helped students easily handle understanding instructions of ABL and the Trigonometric functions unit taught during the observed classes where activities from Toolbox were utilized.
Keywords: Education; Math - Teaching & Learning.; Math -- Activity Toolbox.; Activity-based learning.